Frequency of Diabetic Retinopathy and its Association with Hypertension in Patients of Type-II Diabetes Mellitus - Ashfaq Ahmed, Aftab Hussain Abro, Ali Nawaz Bijarani, Ata ur Rehman, Kiran Khan, Naveed Nayyer, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Poorly controlled diabetes is associated with numerous complications, primarily resulting from vascular damage. The coexistence of hypertension has been shown to further exacerbate diabetic complications. In Pakistan, an estimated 20–60% of individuals suffer from both diabetes and hypertension concurrently, significantly increasing the risk of adverse outcomes. Therefore, the present study aimed to find out the association between hypertension and the development of diabetic retinopathy in our population. Methods: A case–control study was carried out in the Department of Internal Medicine at Bahawal Victoria Hospital, Bahawalpur. Laboratory investigations included fasting blood glucose, random blood glucose, and glycosylated hemoglobin (HbA1c) levels. Blood pressure measurements were done. Screening for diabetic retinopathy was performed by fundoscopic examination. SPSS version 20 was used to analyse the data. A p-value of less than 0.05 was considered statistically significant. Results: The mean age of participants in Group A was 51.7 ± 9.4 years, whereas in Group B it was 49.5 ± 8.7 years. A longer duration of diabetes was observed in Group A compared with Group B. Higher blood glucose levels were more commonly associated with the development of diabetic retinopathy in Group A, with mean fasting blood sugar of 159.11 ± 9.42 mg/dL and random blood sugar of 182.39 ± 10.12 mg/dL. Overall, approximately 40% of the diabetic patients were also hypertensive. Systolic hypertension showed a strong and statistically significant association with diabetic retinopathy, with a p-value of 0.001. Conclusion: The present study demonstrated a strong positive association between diabetic retinopathy and hypertension. In addition to other established risk factors, hypertension should be recognized as an important modifiable determinant in the development and progression of diabetic retinopathy. Keywords: Diabetes mellitus, Diabetic retinopathy. Hypertension